Active Male Smoker with Active Pulmonary Tuberculosis, COPD, Covid-19, Klebsiella Pneumonia, Multiple Bullae and Secondary Bilateral Pneumothorax - Mohammad Faridza Setyo Hadikusumab; Susanthy Djajalaksana; Rezki Tantular; Dini Rachma Erawati (Universitaas Brawijaya, 2025)
Introduction: The first reported case in the world of an active male smoker with active pulmonary tuberculosis, chronic obstructive pulmonary disease (COPD), Covid-19, Klebsiella pneumonia, multiple bullae and secondary bilateral pneumothorax. The clinical presentation of secondary bilateral pneumothorax is highly variable, ranging from mild shortness of breath to tension pneumothorax and can result in very severe conditions. This case report aims to discuss the clinical challenges, diagnostic, and treatment approach, as well as follow-up of a male smoker diagnosed with active pulmonary TB, COPD, Covid-19, Klebsiella pneumonia, multiple bullae, and secondary bilateral pneumothorax. Case: Patient’s history, physical examination, supportive examination, and management strategies were documented and analyzed. A 47-year-old male active smoker with a history of shortness of breath in the last 2 weeks which has gotten worse since the last 1 day. The patient came to Lawang Hospital, an x-ray showed left tension pneumothorax, then was referred to Saiful Anwar Hospital. CXR from Saiful Anwar Hospital shows bilateral pneumothorax with left tension pneumothorax. The patient underwent two chest tube insertions with an interval of 2 days between insertions. The covid-19 PCR results were positive. Sputum bacteriological test showed Klebsiella pneumoniae infection. Thorax CT-scan with contrast showed multiple cysts and bullae on bilateral hemithorax and bilateral ground glass opacity on tree in bud with suspected active pulmonary TB. The bacteriological examination for tuberculosis was negative with a suspicion of COPD due to an active smoking habit. The patient is still being treated with anti-tuberculosis drugs, antibiotics, and antivirals, and showed improvement. Conclusion: Cases of secondary bilateral pneumothorax with active pulmonary TB, COPD, Covid-19, Klebsiella pneumonia, multiple bullae in active smoking patients with subtle clinical features are quite rare, which frequently results in misdiagnosis during thoracic assessments and may exacerbate the patient's condition. Clinicians must remain vigilant for potential underlying diseases in such cases.